Mineralogical and Geochemical Characteristics of the Utanobori Gold Deposit in Northern Hokkaido, Japan. Issue 4 (13th August 2019) - Sorulen, Thomas T.; Takahashi, Ryohei; Tanaka, So; Suzuki, Kana; Imai, Akira; Watanabe, Yasushi; Kikuchi, Shingo
Abstract: The Utanobori gold deposit is a low‐sulfidation, epithermal vein‐type deposit located in northern Hokkaido, Japan. The deposit is hosted by conglomerate, sandstone, and tuff of the Middle to Late Miocene Esashi Formation. These rocks were hydrothermally altered. Silica sinters and quartz‐adularia veins are common in the deposit. The quartz‐adularia veins either contain a ginguro band, which corresponds to the main gold‐bearing vein (Type 1 Veins), or do not contain a ginguro band but contain minor adularia (Type 2 Veins). Type 1 Veins are divided into three stages with 12–14 substages. Ore minerals identified include electrum, naumannite, chlorargyrite, bromargyrite, an unidentified Fe‐Sb mineral, and an Fe‐(Sb)‐As mineral. These ore minerals formed in the main mineralization stages I (bands I‐b and I‐d) and II (band II‐a). Scanning electron microscopy with cathodoluminescence images show that cathodoluminescence‐dark microcrystalline quartz exhibiting colloform (ghost‐sphere) texture is closely associated with ore minerals in the Type 1 Vein and Type 2 Vein, and the Al and K contents of such quartz are commonly >1000 ppm. This indicates that the ore minerals were crystallized from alkaline, silica‐saturated fluids at temperatures <200°C, which initially deposited amorphous silica that was recrystallized to microcrystalline quartz. The average Au content of electrum is 52.5 at% Au ( n = 10), 65.7 at% Au ( n = 20), and 55.5 at% Au ( n = 5) in bands I‐b, I‐d, and II‐a, respectively, of Type 1 Veins. The δ 34 SCDT values of two fine‐grained disseminated pyrites in the altered conglomerate and bedded tuff in the argillic altered zone are −4.3 and −4.2‰. Ar‐Ar dating on adularia yielded 13.6 ± 0.06 Ma, 13.6 ± 0.07 Ma, and 13.6 ± 0.06 Ma for the stages I, II, and III of the Type 1 Vein, respectively. K‐Ar ages determined on adularia in the silica sinter and on whole‐rock of glassy rhyolite of the Esashi Formation are 15.0 ± 0.4 Ma and 14.6 ± 0.4 Ma, respectively. These radiometric ages indicate that silica sinter associated with the rhyolitic volcanic rocks formed prior to the main gold mineralization. Abstract : This study shows that ore minerals were crystallized from alkaline, silica saturated fluids at temperatures <200°C that initially precipitated amorphous silica which eventually crystallized to microcrystalline quartz.